Cover Picture: Synthesis, Characterizations, Magnetism and Thermal Degradation of a 2‐Fold Interpenetrated 3D Cobalt‐Organic Framework (Chin. J. Chem. 3/2014). Issue 3 (March 2014) - Yang, Linyan; Xin, Liangliang; Gu, Wen; Liao, Shengyun; Du, Peiyao; Tian, Jinlei; Zhang, Yanping; Lv, Rui; Wei, Xiaohua; Liu, Xin; Liao, Daizheng
<x xml:space="preserve">Abstract</x> The cover picture shows a new coordination polymer, [Co2(L)2(4, 4′‐bipy)]n·3nH2O (1) based on 5‐(3‐methyl‐5‐phenyl‐4H‐1, 2, 4‐triazol‐4‐yl)isophthalic acid (H2L) and 4, 4′‐bipyridine (4, 4′‐bipy), which has been hydrothermally synthesized and characterized by single‐crystal X‐ray diffraction, XRPD, IR, and elemental analysis. The 2D triangle networks were linked by the bridging 4, 4′‐bipy ligand to give rise to a 2‐fold interpenetrated 3D architecture. We can define Co(II) ions as 4‐connected nodes and the L2− ligands as 3‐connected nodes. Thus, the 3D structure can be described as a 2‐fold parallel interpenetrated ins InS 3, 4‐conn topology. Variable‐temperature (2–300 K) magnetic susceptibility measurements indicate that compound 1 exhibits antiferromagnetic interactions between the Co(II) paramagnetic centers. Compound 1 was heated to produce Co3O4. The particle size of the Co3O4 phase is 400–800 nm. More details are discussed in the article by Liu et al. on page 227–232.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>